Consumidor de mídias móveis : a influência do perfil do adotante na relação entre valor percebido e intenção de compra - Santos, Washington Romão dos (2014)
The present study aims to evaluate if the profile of the adopter of innovations affects the relationship between Perceived Value and Intention to Buy mobile media (smartphones, tablets, ultrabooks and e-readers). This is a quantitative study that seeks to